Comparative Study Thymol Oiland Some Gel Face Washing on Resistance Propionibacterium A - Mais E.Ahmed; Jenan A.Ghafil; Walaa Najim (Institute of Medico-legal Publications Pvt Ltd, 2021)
Acne is elevated of skin secretion with hyperkeratosis causing Propionibacterium acnes. The goal of studywas to assess the anti-inflammatory, and antibacterial potential of Thymol oil compare Gel face ,and isthemain bacteriuminvolved in the acne. The unpredictable use of antibiotics for the treatment of acne may endup within theadvancement of bacterial resistance.